A path to a dynamic hydrogen storage system using a liquid organic hydrogen carrier (LOHC): Burner-based direct heating of the dehydrogenation unit. (8th January 2023) - Bollmann, Jonas; Schmidt, Nikolas; Beck, Dominik; Preuster, Patrick; Zigan, Lars; Wasserscheid, Peter; Will, Stefan
Abstract: Liquid organic hydrogen carrier (LOHC) systems offer a promising way to store and transport hydrogen in a safe and dense form at ambient conditions. Compared to other chemical hydrogen storage systems such as ammonia, formic acid, and methanol, LOHC systems enable reversible storage of hydrogen. For the endothermic hydrogen release reaction, heat and a suitable catalyst are needed. In this work for the first time, the exhaust gas enthalpy of a porous media burner is utilized to supply the heat for dehydrogenation of the LOHC compound perhydro dibenzyltoluene (H18-DBT). This approach significantly increases the system dynamics and the power density of the dehydrogenation unit compared to conventional heating via a heat transfer fluid. A dynamic hydrogen release is important to satisfy the fluctuating hydrogen demand, especially in hydrogen refuelling stations (HRS) or in stationary heating applications, e.g., for buildings. Our setup utilized methane as fuel source for the burner. The key challenge is the precise temperature control of the direct heating of the LOHC in the dehydrogenation unit. This is required as hot spots may result in thermal decomposition of the LOHC compounds, while cold spots limit the rate of the dehydrogenation reaction. With our laboratory-scale setup, we demonstrate a hydrogen release from H18-DBT of up to 450 mlN min −1 with 8.2 g of Pt on alumina catalyst (0.3 mass % Pt loading, i.e., 25 mg of Pt). Hydrogen is released within 10 min after a cold start of the entire system. The system exhibits a catalyst productivity of up to 1.5 gH2 gPt −1 min −1 and a power density relative to the reactor volume of about 3.6 kWtherm L −1 based on the lower heating value of hydrogen. Our findings show the strong potential of the direct heating concept in hydrogen release from LOHC systems and represent a significant step towards LOHC-based technical hydrogen provision systems. Highlights: Dehydrogenation of a LOHC using the exhaust gas enthalpy of a porous media burner. LOHC heating rates in the dehydrogenation unit of about 60 K min −1 . Catalyst productivity of 1.5 gH2 min −1 gPt −1 for 18% degree of dehydrogenation. Power density of the dehydrogenation unit of about 3.6 kWtherm L −1 .